1999
DOI: 10.1103/physrevlett.82.859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhomogeneity on Spiral Wave Dynamics

Abstract: The effect of weak inhomogeneity on spiral wave dynamics is studied within the framework of the two-dimensional complex Ginzburg-Landau equation description. The inhomogeneity gives spatial dependence to the frequency of spiral waves. This provides a mechanism for the formation of a dominant spiral domain that suppresses other spiral domains. The spiral vortices also slowly drift in the inhomogeneity, and results for the velocity are given. [S0031-9007(98)08283-0] PACS numbers: 82.40.Ck, 47.32.Cc, 47.54. + r S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 17 publications
(16 reference statements)
0
17
0
Order By: Relevance
“…[3][4][5] In a capillary containing a self-oscillating gel that hosts the photosensitive Belousov-Zhabotinsky reaction (BZR), mechanical oscillations of the gel under nonuniform illumination, which controls the spatial distribution of oscillation frequency, can cause either photophobic or phototropic movement of the gel as a result of this mechanism. 6 For rotating spiral waves, frequency dominance depends on the direction of motion perpendicular to the spiral rotation; outwardly and inwardly rotating spiral waves show highand low-frequency dominance, [7][8][9][10] respectively. When oscillators are arranged along a tube with continuous variation of species concentrations in a diffusion-fed gel, 11 multiplescale growth instabilities of pulse wave propagation are generated, which is caused by the decrease in frequency along the tube.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In a capillary containing a self-oscillating gel that hosts the photosensitive Belousov-Zhabotinsky reaction (BZR), mechanical oscillations of the gel under nonuniform illumination, which controls the spatial distribution of oscillation frequency, can cause either photophobic or phototropic movement of the gel as a result of this mechanism. 6 For rotating spiral waves, frequency dominance depends on the direction of motion perpendicular to the spiral rotation; outwardly and inwardly rotating spiral waves show highand low-frequency dominance, [7][8][9][10] respectively. When oscillators are arranged along a tube with continuous variation of species concentrations in a diffusion-fed gel, 11 multiplescale growth instabilities of pulse wave propagation are generated, which is caused by the decrease in frequency along the tube.…”
Section: Introductionmentioning
confidence: 99%
“…In the following study we will set a 1 = b 1 = c 1 = 1, Ω 1 = 0 for numerical simulations without mentioning and all the theoretical formulas are given generally for 12 parameters. Without the interface interaction, the two media have their single-domain planar wave solutions [2,17] A…”
mentioning
confidence: 99%
“…In oscillatory media such as CGLE, the situations seem a little complex. In some cases, the faster one suppresses the slower as in excitable media; while in other situations, the slower waves are able to dominate the faster ones [35,36]. To our best knowledge, a systematical study on rules of wave competition in terms of phase velocity (e.g., outgoing waves vs ingoing waves, ingoing waves vs ingoing waves and etc.)…”
Section: Ingoing and Outgoing Target Waves In The Complex Ginzburg-lamentioning
confidence: 98%
“…It has been shown that the motion of the domain walls between waves at least in the framework of CGLE satisfies the following relation [35] …”
Section: Ingoing and Outgoing Target Waves In The Complex Ginzburg-lamentioning
confidence: 98%